Impact of hygiene training on dairy cows in northeast India - Melin, D. (Swedish University of Agricultural Sciences, 2015)
Mastitis in dairy cows is an emerging and challenging disease in the tropics, including India. Nation-wide reports suggest that the incidence of clinical mastitis varies from 3.94% to 23.25%, and for subclinical mastitis from 15.78% to 81.60%. In Assam, a northeastern province of India, dairy is an essential part of the mixed farming system that exists in the state, but the milk yield is far below domestic standards. In 2009-2010, International Livestock Research Institute (ILRI) and local associates started to develop a training program for local farmers in Assam, in order to enhance the informal bovine dairy sector in and around Guwahati, India. The project continued until mid-2013. This study was conducted in order to investigate the prevalence of clinical and subclinical mastitis in dairy cows based on the California Mastitis Test (CMT) and clinical examination of the udder, in trained as well as untrained farms, to see if the hygiene training had led to lower disease burden. The objective also included getting an understanding of the pathogens involved, cow factors associated with higher CMT scores and comparing trained with untrained farms regarding milk production and hygiene routines. A questionnaire survey was conducted on 73 trained and 76 untrained farms. From these, 25 trained and 25 untrained farms were chosen for additional CMT and clinical examination of the udder, on 25% of the lactating cows on the farm. Noted parameters for each cow included stage of lactation, parity number and udder hygiene. In total 178 cows were screened. Cows with a CMT score of 3 or more were considered positive and subjected to a milk test for bacterial evaluation. The results were analyzed by descriptive statistics, χ2–test and t-test. At cow level, 6.2 % suffered from clinical mastitis, while 50.6 % suffered from subclinical mastitis in at least one of the quarters (n=178). At quarter level, 1.6 % suffered from clinical mastitis, while 26.6 % suffered from subclinical mastitis (n=700). The mean CMT score among all cows was 2.08 (1-5). A near significant association existed (p=0.08) in CMT score in trained/untrained farms, indicating a lower CMT score in trained farms. The results from the bacterial analysis show that on quarter level for subclinical mastitis (n=184), coagulase-negative staphylococci (n=56) were the most common, followed by Streptococcus agalactiae (n=42), negative growth (n=42), Staphylococcus aureus (n=14), mixed growth (n=13), Streptococcus dysgalactiae (n=10) and ‘streptococci, other’ (n=7). On quarter level for clinical mastitis (n=11), S. agalactiae (n=4) and negative growth (n=4) were most common, followed by S. aureus (n=2) and coagulase-negative staphylococci (n=1). All S. aureus bacteria were tested for penicillinase production; all were negative. A near significant association (p=0.06) existed between CMT score and lactation stage, indicating a higher CMT score in later lactation stages. A near significant association (p=0.06) also existed between CMT score and parity number, indicating a general tendency against higher CMT scores for higher parity numbers. No significant association between udder hygiene and CMT score was found in this study. The average milk production in trained and untrained farms was 7.8 and 6.8 liters respectively. A two sample unpaired t-test showed that the difference is significant (p<0.01). The results show that the prevalence of clinical and subclinical mastitis is in harmony with other studies conducted in India and nearby countries. The bacterial testing saw exclusively gram-positive cultures. The significant increase in milk production and the tendency towards lower CMT score in trained farms indicate that the hygiene training has led to positive results for the dairy farmers.